OPTIMALISASI MANAJERIAL SUMBER DAYA MANUSIA DALAM MENINGKATKAN STRATEGI KEUANGAN LEMBAGA PENDIDIKAN PESANTREN: STUDI PENGABDIAN MASYARAKAT DI PESANTREN AR-RAUDLATUL HASANAH 2 LUMUT TAPANULI TENGAH - Sebayang, Abdul Aziz; Suwandi, Suwandi; Harahap, Arridha; Salsabillah, Arida; Ningsih, Alpi Kurnia (STKIP Pesisir Selatan, 2025)
Islamic education will stagnate if its human resources are unable to answer the challenges of the times through innovation and scientific renewal. Therefore, strengthening the capacity of human resources in Islamic boarding schools needs to be a sustainable and systematic strategic agenda. Islamic boarding schools are Islamic educational institutions that have a strategic role in shaping character, leadership, and strengthening Islamic values. However, in facing the challenges of globalization, Islamic boarding schools are required to improve their institutional management capacity, especially in terms of human resources (HR) and finance. This study aims to explore strategies for strengthening HR management and optimizing the management of productive waqf at Ar-Raudlatul Hasanah 2 Lumut Islamic Boarding School through a participatory approach in the form of a forum group discussion (FGD). The results of the thematic analysis showed three main findings: the need for managerial training based on Islamic boarding school values, the importance of professionalizing waqf asset management, and the urgency of technology integration in financial governance. This activity also shows that the participatory approach is effective in building collective awareness and commitment to contextual and sustainable institutional transformation.